Wavelet methods for elliptic partial differential equations - Urban, Karsten (Numerical mathematics and scientific computation., 2009)
A text based on the author's course that introduces graduates to the basics of wavelet methods for partial differential equations and describes the construction and analysis of adaptive wavelet methods.